2009
DOI: 10.1111/j.1399-0004.2009.01247_2.x
|View full text |Cite
|
Sign up to set email alerts
|

IFRD1 modulates disease severity in cystic fibrosis through the regulation of neutrophil effector function

Abstract: Identification of IFRD1 as a modifier gene for cystic fibrosis lung disease Gu et al. (2009) Nature 458: 1039–1044

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Analysis of the correlation between IFRD1 polymorphism rs7817 and nasal polyposis in CF patients. (18) . Hector et al (29) observed an up-regulation of IFRD1 expression in human CF neutrophils and found it linked to reactive oxygen species (ROS) production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the correlation between IFRD1 polymorphism rs7817 and nasal polyposis in CF patients. (18) . Hector et al (29) observed an up-regulation of IFRD1 expression in human CF neutrophils and found it linked to reactive oxygen species (ROS) production.…”
Section: Discussionmentioning
confidence: 99%
“…The change from a cytosine to a tymine in the rs7817 polymorphism occurs in the 3' UTR region of the IFRD1 gene (30) . The rs7817 SNP contains a target site for microRNA-577 (miR-577), expressed mainly in neutrophils, and a predicted site for splice enhancement (16,18) . Presently, there is no evidence whether this SNP could alter gene expression or whether the microRNA could alter the protein level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found high expression in human blood cells (SymAtlas, 2008) and Gu et al found highest expression in neutrophils, where up-regulation occurs during the final differentiation steps (Ehrnhoefer, 2009; Gu et al, 2009). The authors suggested that IFRD1 modulates CF lung disease through the regulation of neutrophil effector function, but that other explanations, involving different cell types, should not be ignored.…”
Section: Associating Genes and Insight Into Their Modifying Mechanismsmentioning
confidence: 93%